A conceptual model for developing a measurement tool for hospital food service operation in Malaysia - Osman, Noor Suzana; Md. Nor, Norazmir (Association of Malaysian Environment-Behaviour Researchers (AMER); ABRAmalaysia, 2019)
This study aims to provide and identify the best tools for measuring the quality of food service in Malaysian hospitals. The discussion focuses on the models used to evaluate the performance of food service operation in hospitals, as well as review critiques, issues, and the latest findings. Many tools have been introduced in the previous studies. However, the decision about the best fit tool to measure the quality of hospital food service is still unclear. Future study should be conducted, and an empirical test that examines various dimensions, such as food and meal service quality, staff/service issues and physical environment must be considered in the evaluation.